Pengaruh Profitabilitas dan Leverage Terhadap Nilai Perusahaan - Rugaiya Abdullah; Ilyas Lamuda; Zubaidah Rahman (Jurnal Ekonomi, Manajemen, Ilmu Sosial dan Politik (J-EMSPOL), 2025)
This study aims to determine the effect of profitability and leverage on company value in cigarette companies listed on the Indonesia Stock Exchange, the technical analysis of this research data uses multiple linear regression. This can be seen from the hypothesis test where the value of profitability is significant for the profitability variable (X1) with a significance value of 0.038 because <0.05 which means that the profitability variable has a positive effect. So it can be said that profitability (X1) statistically affects the value of the company (Y) which means that the first hypothesis is accepted, the leverage variable (X2) with a significance value of 0.993 which means> 0.5. So it can be said that leverage (X2) statistically does not affect the value of the company (Y). The results of this study state that partially, leverage variable (x2) dominantly has no effect on company value in cigarette companies listed on the indonesia stock exchange. this means hypothesis 2 is rejected.